From Diversity to Inclusion: Centring the Voices of Undergraduate Engineering Students - Hanson, Cori (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur)

(untitled) (Canadian Society for the Study of Higher Education, 2022)
Some Canadian undergraduate engineering programs report 30–40% of enrolled students are women. Kanter’s tipping point theory argues that women become less tokenized when they make up 30% of a group’s population. Other scholars have found that in comparable situations, women continued to experience discrimination, hostility, and competition. This critical study provides further evidence against a tipping point for equity by centring the experiences of traditionally underrepresented undergraduate students studying at a faculty of engineering with 35% women undergraduates enrolled. Reflective thematic analysis of experiences shared bywomen, racialized students, 2SLGBTQ+ students, and students from lower socio-economic statuses found instances of discrimination, varying perceptions of capabilities, and inequitable access to support, community, and on-campus leadership roles. Therefore, institutions need to acknowledge the intersectional experiences of students and work toward changing campus culture in addition to diversity efforts.